Analisis Muatan Karakter Cinta Tanah Air Pada Buku Siswa Kelas 4 SD Tema Indahnya Keragaman Di Negeriku - syiffa khairunnisa zahra; Iis Nurasiah; Arsyi Rizqia Amalia (Jurnal Gentala Pendidikan Dasar, 2021)
The study was intended to describe the load of patriotic character on the fourth grade school elementary school student book the beautiful theme of diversity in my country. The design on this research is qualitative research. The type of research used is a descriptive qualitative. Research methods used are those of content analysis. The data retrieved on this study is the content of a character love of the motherland in the sentences found in the student book on IPS materials. The source of data on this study is the 2013 curriculum of the 2013 beautiful them of diversity in my country, the 2017 revision on the fourth grade school elementary school. The study was carried out from April to June. The data analisyis techniques involve data reduction, data display divided into two stages, the classifying of data, the descryption and interpretation of data, and the conclusions drawing/verification. An analysis of the fill character content found in the fourth grade school elementary school students book the beautiful theme of my country was found as many as 77 load of patriotic character covering 15 sentences in the first indicator, 22 sentences in the second indicator, 22 sentences in the third indicator, 9 sentences in the forth indicator, 5 sentences in the fifth indicator, 4 sentences in the sixth indicator. The sentences found in each material can grow and form a patriotic love character in the student. By teaching and delivering material that is sufficient.